Fluxo, corpo e percepção na comunicação digital - Braga, Eduardo Cardoso (2007)
There are different ways of conceiving the image in the digital communication. When investigating some discourses regarding the digital image, we came across some constant: the prevalence of the vision (ocularcentrism) and the absence of body reference (disembodiment). The digital image is conceived as simulacrum (Baudrillard), as disembodiment (Kittler), or phenomenon without reference (Mitchell). Moreover, in many of the discourses about communication, one conceives a homogeneous space of absolute transparency, in which obstacles do not exist, either conflicts, or differences (Vattimo). In our thesis we assert that the reasons of those conceptual marks are the slight knowledge of simulacrum, deriving from the Platonism; of representation, deriving from the Cartesianism; of transparency, deriving of the Neoplatonism. We mainly investigate those conceptual traditions with respect to the concept of image and the epistemic statute of the perception. We established a connection between some visual experiences of the past and the new possibilities disposed by the digital technologies. We then looked for new philosophical bases that could set the image free from inferior epistemic condition. The Bergson s phenomenology fed the thinking of the digital image and the perception as embodiment phenomenon, in which the body has a fundamental role in the significance and in the construction of the subjectivity. Thus, new corporal and subjective dimensions announce themselves and show new ways of man being. Body and subjectivity together in the relation to digital medium open new horizons to think the communication and the epistemic statute of the digital image as a knowledge possibility